DESIGN AND OPTIMIZATION OF A REGENERATIVE BRAKING SYSTEM - Zhalelov, Batyrlan; Sailaubek, Yernur; Tnymkulov, Rustem; Turaly, Nurbek (Nazarbayev University School of Engineering and Digital Sciences, 2024)
The research was conducted to explore a unique modern method of recuperation called the regenerative braking system. The concept behind that is to generate voltage from the source of heat. The device that was used in our case is a Thermoelectric generator(TEG). This device converts the temperature difference into the potential difference. As the braking is performed, there is an enormous amount of energy that is just dissipated in the rotor, and released to the environment. The study explores the way to implement the TEG into the braking system, find the best possible assembling approach, and discover whether the output parameters are going to be sufficient for the implementation of helpful systems. In order to achieve the aims that were set, simulations, as well as hand calculations were applied. Results were obtained by using different softwares such as ANSYS, Solidworks, MATLAB and Excel. From the presented data, the analysis of the selected design was executed. Figuring out the applications that can be theoretically implemented with the help of regenerative braking systems, as well as the conditions in which they are the most effective
Keywords: Type of access: Open access